Pelatihan Pembuatan Eco-Friendly Detergen Daun Balik Angin (Alphitonia Excelsa) pada Kelompok Ibu-ibu di Desa Mandi Angin - Kurdiansyah; Muhammad Faisal Machdie; Gusti Abdul R. Thamrin (Institut Pertanian Bogor, 2021)
Special Purpose Forest Area (KHDTK) Lambung Mangkurat University is a forest area with types of plants and trees. KHDTK is close to residential areas. The existence of community activities around KHDTK will indirectly have an impact on the sustainability of KHDTK. The community activities that impact KHDTK are bathing, washing, and latrine activities (MCK). This community activity provides insight into the impact of using chemical detergents on health and the environment, as well as increasing community empowerment around the KHDTK area in processing natural resources in the form of processing leaves into environmentally friendly detergents. The implementation method consists of two steps, the first step is counseling, and the second step is the preparation of eco-friendly detergents. Counseling carried out by providing knowledge about the impact of synthetic detergents and the manufacture of environmentally friendly detergents. In this activity, the active ingredients used are balik angin leaves because these leaves contain saponins. Leaves balik angin extraction using the infusion method. The results of the evaluation of the activities showed an increase in public knowledge about the impact of synthetic detergents on the environment and an increase in community skills in making environmentally friendly detergents. This activity is very useful in increasing the knowledge and skills of the community.